Agricultural Productivity through Rural Assets: Evaluating MGNREGA’s Role in Boosting Agricultural Performance in India - Tripathi, Sandeep; Yadav, Pushpender; Bharne, Saurabh; Tiwari, Hariom (Indian Journal of Extension Education, 2025)
The study evaluated the agricultural productivity effects of rural infrastructure investments and employment provision under the Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) in India. The study assesses how public works, such as land development, micro-irrigation, drought-proofing, and rural connectivity, support key agricultural outcomes, including cultivated area, crop yield, and total production. Using state-level panel data from 2016 to 2023 and applying both fixed and random effects models, the study rigorously accounts for state-specific heterogeneity and time-invariant factors, ensuring unbiased and policy-relevant estimates of MGNREGA’s impact on agriculture. The empirical findings demonstrate robust positive effects of MGNREGA-facilitated assets, particularly land development, drought-proofing, water conservation, and micro-irrigation, on key agricultural performance indicators. Notably, localised employment generation, as indicated by person-days of employment, emerges as a critical enabler of enhanced productivity. These findings highlight the potential of MGNREGA not merely as a welfare initiative but as a catalytic policy tool for agricultural enhancement. The research underscores the value of integrating rural employment schemes with agronomic needs to improve productivity, stabilise output, and support sustainable rural livelihoods in India’s agrarian economies.